Assessment of natural ventilation effectiveness for an active NetZero energy house. Issue 2 (3rd April 2017) - Ellis, J.; Schwartz, J.; Mora, R.
ABSTRACT: This study was undertaken to investigate the effectiveness of an integrated natural ventilation design for a NetZero energy house in maintaining occupants comfortable solely by passive means. The house was instrumented and monitored during the warmest months of the year. A dynamic thermal model and a computational fluid dynamics (CFD) model were developed to supplement the measurements and help to understand the factors that contribute to the effectiveness of the design. A methodology was developed to validate the models with data and cross-validate them. Adaptive thermal comfort is used as the metric to determine if comfort has been achieved. The study concludes that the house as a whole meets the comfort target. Two technologies were compared through simulations to evaluate their effect on enhancing wind-induced natural ventilation. The technologies did not improve cooling performance in a significant manner. Further work is needed to improve the models through technologies testing in the laboratory and model the uncertainty of the boundary forces to increase confidence in the results.